Influence of power Doppler gain setting on Virtual Organ Computer-aided AnaLysis indices in vivo: can use of the individual sub-noise gain level optimize information? - Collins, S; Stevenson, G; Noble, J; Impey, L; Welsh, A (2012)
OBJECTIVES: To demonstrate the influence of gain setting on the calculated Virtual Organ Computer-aided AnaLysis (VOCAL(™)) three-dimensional (3D) indices and define a point, the sub-noise gain (SNG), at which maximum information is available without noise artifact. METHODS: Pregnant women were recruited at the time of their pregnancy-dating scan. Five identical static 3D power Doppler volumes of the placenta were acquired using identical machine settings apart from altering the power Doppler gain setting. The gain settings included the individualized SNG setting (determined by increasing gain until noise artifact was visible, then reducing it until the artifact just disappeared). The data were analyzed using VOCAL II. Vascularization index (VI), flow index (FI) and vascularization flow index (VFI) were calculated for the same sample at five different power Doppler gain levels. The relationship between the values calculated for the VOCAL indices and the gain value was explored using linear regression analysis. RESULTS: Results from 50 women were analyzed. The percentage difference in VI and VFI from that observed at the SNG level in each woman was significantly linearly related to the gain setting relative to that at the SNG point (VI: r(2) = 0.68, P < 0.0001; VFI: r(2) = 0.72, P < 0.0001), with the values produced for VI and VFI decreasing as the gain was turned down. There was a distinct 'turning point' at the SNG level with linear relationships above and below, but with significantly different gradients (P ≤ 0.001). This relationship was not demonstrated for FI. CONCLUSION: The SNG setting appears to represent each individual's optimum gain level. Using this may improve meaningful comparisons of VI and VFI between patients.